Methodological Analysis of the Transformation of Contemporary Fiqh Muamalah Practices at Maahad Vokasional Aman Bistari Selangor - Nuraini, Afifah; Fathudin; Ariyanti, Rini (Al-Bayyinah, 2025)
This study investigates the transformation of contemporary fiqh muamalah practices at Maahad Vokasional Aman Bistari Selangor (MVABS), focusing on the dynamics of ijtihad jamā‘ī and the methodologies of legal reasoning (istinbāṭ al-ḥukm) in addressing challenges arising from modern economic transactions. The research is driven by the need to bridge the epistemological gap between classical Islamic legal thought and the realities of digital finance and global Islamic economics. Adopting a qualitative case study design, data were obtained through in-depth interviews, participant observation, and document analysis, then examined using thematic analysis. The findings reveal a distinctive model of collective ijtihad that integrates maqāṣid al-sharī‘ah principles with the operational mechanisms of contemporary financial systems. This integration has resulted in a contextualized framework of fiqh muamalah that supports the formulation of adaptive legal opinions (fatāwā) aligned with modern socio-economic realities. The study’s novelty lies in demonstrating how a vocational-based pesantren can function as a living laboratory of Islamic law, producing dynamic, applicable jurisprudence while maintaining fidelity to classical traditions. Conceptually, this research contributes to the development of living fiqh theory in Islamic education, and practically, it provides a replicable model for designing responsive Islamic legal and economic governance in the digital era.